PROPOSED MARKETING STRATEGY FOR FRANCHISE COFFEE SHOP (STUDY CASE: BENGRAS KOPI IN BANDUNG) - Wise Maliha, Dabitha
As the fourth largest coffee producers in the world, Indonesia become one of the most potential market for the entrepreneurs to entry coffee shop industries. Nevertheless, one of small business local coffee shop in Bandung, Bengras Kopi. The phenomenon of coffee as the local wisdom in Indonesia encourage their vision to promoting the originality of Indonesian coffee. Moreover, this company has desire to expanding their market through franchise system. However, Bengras Kopi got many obstacles to sustaining their business. In 2015, this coffee shop had nine branches and only two were keep existed. Then in 2016, this company started to build management team and ready to improve their franchising system. Currently, Bengras Kopi have five branches which located in Banjaran, Ciparay, Soreang, Telkom-Uni, and Padang City. This research aims to help Bengras Kopi’s team in Bandung improve the standardization of franchise system in marketing strategy. To identify the problems in external analysis, this research use general environment analysis, industry environment analysis and competitor analysis. For internal analysis, this research use STP analysis, marketing mix, business model canvas, value chain and customer analysis. Furthermore, this research uses quantitative methods that collecting data based on questionnaires with total 113 customers as the respondents. Based on these analysis, this research find the current situation of this company is survival stage. On this stage, Bengras Kopi need to develop their franchising system through business format and business level strategy. Therefore, this research uses format components and centrality as tools for business format. Furthermore, this research also recommend Bengras Kopi to implementing the cost leadership strategy in value chain activities. Lastly, this research also uses TOWS matrix as the main tools to develop marketing activities. In conclusion, this research proposes strategy map, timeline activities and budgetting as the implementation plan.